Hoarding among older people: an evaluative review. (9th November 2016) - Thew, Graham R.; Salkovskis, Paul M.
Abstract: While there is considerable evidence that the factors involved in hoarding typically begin to manifest early in life (mostly in adolescence), the majority of those sampled in research studies are in their later years. As so much of our understanding of the psychological factors involved in hoarding is derived from those who are older and more chronically affected, the core hoarding psychopathology may have been masked, overlaid or even disregarded in previous research and in our approaches to clinical intervention. That is, factors relating primarily to chronicity of the problem and feelings of demoralization, hopelessness, loss and the extent of the damage caused to the person's life may swamp the processes which led to and maintain the problem. The present review examines the extent to which this is so and considers theoretical and clinical implications. The literature relevant to hoarding in later life was reviewed evaluatively in relation to a number of questions placing hoarding in a lifespan developmental context. Many studies relied on purely descriptive methodologies, meaning that typical case presentations and case histories are well documented, with less attention paid to underlying causal and maintaining mechanisms. Efforts to identify and control for factors relating to age or problem chronicity were minimal. A key future direction is the identification of younger samples of people who hoard in order to identify more clearly the processes which drive acquisition and retention of excessive amounts of material.